Endocentric Phrases in Mesut Kurtis' album Tabassam (2004): Tagmemeik Kenneth Lee Pike - Haque, Arina; Azzadi, Rusda Fauziah; Maimunah, Iffat (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The purpose of this research is to describe the form of endocentric phrases in Mesut Kurtis' Tabassam album and to describe its construction based on Kenneth Lee Pike's tagmemic units. This research is qualitative descriptive research, with the data source of the song lyrics in Mesut Kurtis' Tabassam album. The data collection technique uses the reading-note technique. Data validation techniques by increasing persistence, triangulation, and discussion. Data analysis techniques by collecting data, processing data, reading the entire data, grouping data, and describing the data. The results of this study reveal that the song lyrics on the Tabassam Album by Mesut Kurtis, which consists of 13 songs, contain endocentric phrases with three types, namely: (1) attributive endocentric phrases with a total of three phrases; (2) a three-phase coordinative endocentric phrase; and (3) a positive endocentric phrase with a single phrase. The three types of phrases have various structures. Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ ÙˆØµÙ Ø´ÙƒÙ„ Ø§Ù„Ø¹Ø¨Ø§Ø±Ø§Øª Ø§Ù„Ù…Ø±ÙƒØ²ÙŠØ© ÙÙŠ Ø£Ù„Ø¨ÙˆÙ… Ù…Ø³Ø¹ÙˆØ¯ ÙƒÙˆØ±ØªÙŠØ³ ØªØ¨Ø§Ø³Ù… ÙˆÙˆØµÙ Ø¨Ù†Ø§Ø¦Ù‡ Ø¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ ÙˆØØ¯Ø§Øª ØªØºÙ…ÙŠÙ…ÙŠÙƒ Ù„ÙƒÙŠÙ†ÙŠØ« Ù„ÙŠ Ø¨Ø§ÙŠÙƒ. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø¨ØØ« ÙˆØµÙÙŠ Ù†ÙˆØ¹ÙŠ ØŒ Ø¨Ù…ØµØ¯Ø± Ø¨ÙŠØ§Ù†Ø§Øª ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ø£ØºÙ†ÙŠØ© ÙÙŠ Ø£Ù„Ø¨ÙˆÙ… Ù…Ø³Ø¹ÙˆØ¯ ÙƒØ±ØªÙŠØ³ ØªØ¨Ø³Ù…. ØªØ³ØªØ®Ø¯Ù… ØªÙ‚Ù†ÙŠØ© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø£Ø³Ù„ÙˆØ¨ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù…Ù„Ø§ØØ¸Ø§Øª. ØªÙ‚Ù†ÙŠØ§Øª Ø§Ù„ØªØÙ‚Ù‚ Ù…Ù† ØµØØ© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø²ÙŠØ§Ø¯Ø© Ø§Ù„Ù…Ø«Ø§Ø¨Ø±Ø© ÙˆØ§Ù„ØªØ«Ù„ÙŠØ« ÙˆØ§Ù„Ù…Ù†Ø§Ù‚Ø´Ø©. ØªÙ‚Ù†ÙŠØ§Øª ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆÙ…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆÙ‚Ø±Ø§Ø¡Ø© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ù„ÙƒØ§Ù…Ù„ ÙˆØªØ¬Ù…ÙŠØ¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆÙˆØµÙ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª. ÙˆØªÙƒØ´Ù Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ø£ØºÙ†ÙŠØ© ÙÙŠ Ø£Ù„Ø¨ÙˆÙ… ØªØ¨Ø§Ø³Ù… Ù„Ù…Ø³Ø¹ÙˆØ¯ ÙƒÙŠØ±ØªØ³ ØŒ ÙˆØ§Ù„Ù…ÙƒÙˆÙ†Ø© Ù…Ù† 13 Ø£ØºÙ†ÙŠØ© ØŒ ØªØØªÙˆÙŠ Ø¹Ù„Ù‰ Ø¬Ù…Ù„ Ù…Ø±ÙƒØ²ÙŠØ© Ø°Ø§Øª Ø«Ù„Ø§Ø«Ø© Ø£Ù†ÙˆØ§Ø¹ ØŒ ÙˆÙ‡ÙŠ: (1) Ø¬Ù…Ù„ Ù…Ù†Ø³ÙˆØ¨Ø© Ø¯Ø§Ø®Ù„ÙŠØ© Ø¨Ù…Ø¬Ù…ÙˆØ¹ Ø«Ù„Ø§Ø« Ø¬Ù…Ù„. (2) Ø¹Ø¨Ø§Ø±Ø© Ù…Ø±ÙƒØ²ÙŠØ© Ø¯Ø§Ø®Ù„ÙŠØ© ØªÙ†Ø³ÙŠÙ‚ÙŠØ© Ø«Ù„Ø§Ø«ÙŠØ© Ø§Ù„Ù…Ø±Ø§ØÙ„ Ø› Ùˆ (3) Ø¹Ø¨Ø§Ø±Ø© Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© Ù…ØªÙ…ØÙˆØ±Ø© ØÙˆÙ„ Ø§Ù„Ø°Ø§Øª Ù…Ø¹ Ø¹Ø¨Ø§Ø±Ø© ÙˆØ§ØØ¯Ø©. Ø§Ù„Ø£Ù†ÙˆØ§Ø¹ Ø§Ù„Ø«Ù„Ø§Ø«Ø© Ù…Ù† Ø§Ù„Ø¹Ø¨Ø§Ø±Ø§Øª Ù„Ù‡Ø§ Ù‡ÙŠØ§ÙƒÙ„ Ù…Ø®ØªÙ„ÙØ©.